Estudio de biofertilizantes con diferentes dosis de aplicación en el desarrollo y producción del cultivo de maní (arachis hypogaea l.) En época lluviosa, en la zona de El Empalme, Provincia del Guayas, 2015. - Vega Pincay, Nelson Enrique (2016)
This research was conducted on site "La Carmela", located in the rural parish of El Rosario, Canton El Empalme, Guayas Province, located at 100 meters above the sea level, located in the geographical coordinates of 79º, 28 ', 30' 'and 01 ° south latitude. The climate is tropical, characterized by an average temperature of 26ºC average annual rainfall of 1600 - 3200mm. relative humidity 82%, and annual heliophany of 895.0 hours / sun, soil silty clay loam and frank pH 6.5. The overall objective of this research was: Test the effect of biofertilizers in the development and production of peanut crop (Arachis hypogaea) in the rainy season, in the area of El Empalme, Guayas province. The specific objectives were to determine the effectiveness of the best treatment in the development and production of peanut crop. Establish the best dose of application in the development and production of peanut crop. Select the best bio-fertilizer in crop development. The factors studied were: organic fertilizers (water hyacinth, vermicompost), each in three doses (40, 80, 120 gr / Plants). He performed the analysis and interpretation of the results is concluded: In the plant height at 25 and 50 days the water hyacinth in doses of 120 gr / plant obtained the best average with 36, 67 and 53, 50 cm respectively. It was noted that there is a differentiation in their ways between organic fertilizers, which affects production and productivity of peanut crop, based on the results indicated that: the water hyacinth in high doses showed higher effectiveness the peanut crop yield because this aquatic plant has an active ingredient high in macro and micro nutrients such as nitrogen, phosphorus, potassium, iron, etc.